Zambia : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Despite Zambia's continued battle with poverty, the authorities have maintained sustained growth and macroeconomic stability during the past decade. 2011 showed robust GDP growth supported by agricultural activities and strong bank credit. But the Executive Board expressed concern over the risks arising from the volatility of copper prices and the delay in implementing measures required to meet the 2012 budget deficit target. Directors recommended strengthening the tax administration and reducing subsidies and incentives for achieving the fiscal targets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet